The static structure of liquid semiconductors NiTe and NiTe2: Preliminary results - Guenay, Seckin D.; Akdere, Uensal; Kosovali, Fatma; Tasseven, Cetin (AMER INST PHYSICS, 2007)
The local structures of liquid NiTe and NiTe2 have been investigated by applying the integral equation theory of liquids, Hypernetted-chain (HNC). Interactions between the constituent ions are modeled via a semi-empirical potential. The three correlation functions and partial structure factors of HNC are compared with available experimental data of neutron diffraction. We also plan to investigate the transport properties of these systems with the molecular dynamic simulation.
Keywords: NiTe; NiTe2; hypemetted-chain; semiconductor; Physics